Atlantic cod otolith annual growth increment data 1928-2018 Northeast Atlantic - Steven Campana (Knowledge Network for Biocomplexity, 2022)
Atlantic Cod otolith annual growth increment data for six populations in the Northeast Atlantic (Northeast Arctic, Icelandic, Faroe Islands, Godthaabsfjord Greenland and Sisimiut, Greenland. Full methodological details are provided in Campana et al (2022): Growth portfolios buffer effects of climate change in marine systems.